Randomized controlled phase II trial of S-1 maintenance therapy in Caucasian population with metastatic esophagogastric cancer- the multinational MATEO study - Haag, Georg Martin; Jäger, Dirk (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Chemotherapy including a fluoropyrimidine and a platinum compound is still the mainstay for the majority of patients with esophagogastric adenocarcinoma. The optimal duration of firstline chemotherapy is unknown. In most clinical trials therapy is given until tumor progression or dose-limiting toxicity. Maintenance concepts have been established in other tumor types but not in esophagogastric cancer. S-1 is an oral fluoropyrimidine with proven efficacy in metastatic esophagogastric cancer. Given as a monotherapy S-1 showed a beneficial toxicity pattern.Trial design: MATEO is a randomized, multinational, phase II trial in patients with previously untreated, Her-2 negative metastatic esophagogastric adenocarcinoma. After having completed, without tumor progression, a 12-week induction chemotherapy (including a platinum compound, a fluoropyrimidine with or without a taxane or an anthracycline), 297 patients...